MULTICOMPONENT DIFFUSION IN TERNARY SILICATE MELTS IN THE SYSTEM K2O-AL2O3-SIO2: I. EXPERIMENTAL MEASUREMENTS - Chakraborty S.; Dingwell D.B.; Rubie D.C. (My University, 1995)
We have measured the multicomponent diffusion coefficient matrix, D, for silica rich melts in the system K2O-Al2O3-SiO2 between 1100-1600°C in air. Measurements were done in both peraluminous as well as peralkaline compositions at constant silica content (by weight). A previously untested method for retrieving the full diffusion coefficient matrix, D, from a single diffusion couple experiment was employed successfully.It is found that there is significant coupling between the different oxide components in the melt during diffusion. This coupling may lead to uphill diffusion of a component. Careful microprobe analysis revealed the occurrence of uphill diffusion of all components (not in the same experiment, however) in this study. The nature of coupling is quantitatively treated in a companion paper (Chakraborty et al., 1995). The nature of coupling is the same in peraluminous and peralkaline melts. However, diffusion rates are much faster in peralkaline melts at comparable conditions.The relationship between the elements of the D matrix, Dij, and the effective binary diffusion coefficients (EBDC) are discussed. It is shown that it is possible to describe diffusion in multicomponent melts in terms of EBDC, even if there is strong multicomponent interaction. However, if certain theoretical requirements are not fulfilled, then the EBDC obtained by fitting concentration profiles obtained in diffusion couple experiments may yield spurious results in mass transfer calculations.